Meaning of forgiveness: analysing political and sexual violence cases - Tukela, Anelitha (Department of Sociology, 2023)
This study investigates the meaning of forgiveness in instances of political and sexual violence in contemporary South Africa. Truth Reconciliation Commission (TRC) proceedings about the well known St James church massacre, Brian Mitchell, and Thapelo Mbelo case guide my understanding of the role of forgiveness in instances of political violence. Memoirs and secondary literature revolving around four relatively little-known instances of rape in contemporary South Africa inform my analysis of the role of forgiveness in instances of sexual violence. The study explores what motivated the victims of violence to consider forgiveness and also investigates the role of forgiveness in criminal and social justice. Through comparative work, the research aims to develop a new understanding of the relationship between forgiveness and violence and help the reader understand the purpose of forgiveness in violence, the power it has, and how it helps the victims of violence. Using inspirations from the interpretive sociology, the study draws from the theological and sociological writings which were influenced by sociology of emotions, social psychology, social and political theory, and South African history.